1989
DOI: 10.1007/bf01290104
|View full text |Cite
|
Sign up to set email alerts
|

Shape coexistence at high spin in187Au

Abstract: High-spin states in ~SVAu have been populated in the 172yb(19F, 4n) reaction and studied with in-beam spectroscopic techniques using the "Chateau de Cristal" 4n-multidetector array. A comprehensive level scheme of 187Au has been established. Experimental band crossing frequencies and gains in alignment were deduced. Shape coexistence in 187Au, well established at low spin, is found to survive up to spin 57/2, and manifests itself through well separated oblate and prolate structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…3 where a partial level scheme extracted from [4] is shown. We have measured the y-ray intensities from several gated spectra at 90, 95 and 100 MeV beam energy: we observe that the intensities of the y-rays belonging to the oblate and the prolate systems both increase in the interval of 90-95 MeV though the former increases much faster than the later.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 where a partial level scheme extracted from [4] is shown. We have measured the y-ray intensities from several gated spectra at 90, 95 and 100 MeV beam energy: we observe that the intensities of the y-rays belonging to the oblate and the prolate systems both increase in the interval of 90-95 MeV though the former increases much faster than the later.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations [2,3] using a deformed harmonic oscillator and a WoodsSaxon potential respectively, indicated that this shape coexistence survives up to spin 50 h. Recent experiments [4,5] clearly established that both prolate and oblate shapes survive well separated up to high spin (57/2 h in [4]). …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas the oblate band, developed on the πh 11/2 state is more irregular. Moreover assignement of spins and parities for the observed levels is not obvious; this band would end at spin 27/2 − or 25/2 − depending on the authors [4,5].…”
Section: Negative Parity High Spin Levelsmentioning
confidence: 94%
“…The lighter isotopes are prolate deformed. By adding more and more neutrons, the shape becomes oblate with the quadrupole deformation parameter β 2 [1] taking values β 2 ≤ 0.15 [2][3][4]. A prolate-oblate shape change has been discussed for these nuclei [5][6][7][8][9][10][11].…”
mentioning
confidence: 99%